2022
DOI: 10.1038/s41598-022-11375-6
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study on essential oil compositions, antioxidant, anticholinesterase and antityrosinase activities of three Iranian Artemisia species

Abstract: Artemisia is one of the most diverse genera in the Asteraceae family. The genus is wildly distributed in Irano-Turanian habitats and includes 34 species in Iran. Here, for the first time the essential oil variability, antioxidants and anti-cholinesterase and anti-tyrosinase activities of extracts of three Artemisia species (A. tournefortiana, A. khorassanica, A. haussknechtii), from different regions of Iran were evaluated. Based on GC–MS analyses, 81.84% to 98.70% of the total oils were identified. Cluster an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Various human pathogenic fungi including Candida albicans show susceptibility to the essential oils of Apiaceae plants, cinnamon, lemongrass, clove oil etc. [ 49 , 50 ]. The oil is rich in sesquiterpenoids such as bisabolol , inhibits the growth of Aspergillus niger, A. flavus and Candida species, and thus confirms our findings [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various human pathogenic fungi including Candida albicans show susceptibility to the essential oils of Apiaceae plants, cinnamon, lemongrass, clove oil etc. [ 49 , 50 ]. The oil is rich in sesquiterpenoids such as bisabolol , inhibits the growth of Aspergillus niger, A. flavus and Candida species, and thus confirms our findings [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…2 b). Terpenoids are the most abundant phenolic compounds of essential oil (Table 2 ), because of their redox potential such as free radical scavenging activity, singlet oxygen quenching capacity, and hydrogen donors' activity are associated with the antioxidant activities 35 , 51 , 52 . It was reported that some monoterpenes including carvone and limonene contribute to the antioxidant activity of essential oil.…”
Section: Discussionmentioning
confidence: 99%
“…This process was carried out using a hydro-distillation approach employing a Clevenger-type apparatus under a controlled temperature of 60 °C 21 . The duration of this process was between 3 and 4 h (until the essential oil volume remained constant) 22 , 23 . The essential oil content (Yield) in the lemongrass was calculated by using Eq.…”
Section: Methodsmentioning
confidence: 99%